Iceland's Capital Controls and the Constraints Imposed by the EEA Agreement - VITERBO, Annamaria (Capital Markets Law Journal, 2011)
Capital controls can be used both as emergency measures, to avoid capital flight and help stabilize the exchange rate, and as crisis prevention tools. The web of international economic law treaties to which a State is a party can, however, greatly reduce its policy space to deploy capital controls. In fact, while members of the IMF retain the right to impose capital controls, trade and investment treaties as well as regional agreements require the liberalization of capital movements. In 2008, Iceland introduced strict controls on capital movements, which later became a key component of the programme supported by the IMF Stand-By Arrangement. Are Iceland’s capital controls compatible with the European Economic Area rules? Does an integrated regional legal framework limit the number of emergency tools available at international level for contrasting an economic crisis? TABLE OF CONTENTS: 1. Introduction. - 2. The causes of Iceland's financial and economic crisis. - 3. Iceland's reaction to the crisis. - 4. The implications of Iceland's membership in the EEA for the design of its capital controls regulations. - 5. Final remarks